ANALISIS LEKSEM YANG MENYATAKAN MAKNA RASAPADA PERUT DALAM BAHASA MANDAR (Lexem Analysis Which is Showing that expresses the Sense of Feeling Related to the Stomach in Mandarese) - Haruddin Haruddin (Balai Bahasa Sulawesi Selatan, 2009)
This writing presents lexem that expresses sense of feeling related to the stomach inMandarese. These lexems are identified by using analysis theory of lexical componentmeaning. There are two semantic fields as aoutputs of this brief analysis, namely 1)semantic field with superordinate without the feeling of illness, and 2) semantic fieldwith superordinate that followed by the feling of illness. The two semantic fieldsuncover thirteen lexemsexpressing the related to the stomach in Mandarese.